Development of Islamic Societies in Yoruba Land: Historical Discuss - O. R. Azeez; Zakariyah, Abdulganiyi Abinbade (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Islamic societies in Yoruba land play an effective role in the Yoruba community, where it replace the government in taking care of the affairs of Muslims in another society, these Islamic societies had the variety of names in the Yoruba land, having the same goal and differ in other goals. Thus this research seeks to examine the development of these societies in the Yoruba land, therefore, the researcher divides these Islamic societies into ancient and modern period, then compares the ancient and modern accordingly, and then extracts the results that stipulate the goals of establishing each. For the reader to realize the reality of this research, the researcher uses the descriptive, historical and analytical approach, in which the researcher describes the existence of these societies through the history of its establishment. The researcher believes that the goal of establishing each of these societies is to uphold the word of Allah, spread the teachings and etiquette of Islam among the people of Yoruba land, and repel aggression and injustice against Muslims, because of the challenges of non-Muslims who are with them in society. Finally, the researcher believes that the existence of these Islamic societies in society is neither denied nor rejected, for the great benefits that come from their existence. The researcher advises the heads of the societies to adhere to moderation.